Determination of manganese in vegetables by atomic absorption spectrometry with enrichment using activated carbon - Yaman, M (Instytut Chemii Fizycznej Pan, 1997)
An enrichment method was optimized for the determination of Mn in aqueous solutions and vegetable samples of food origin. Dry ashing and wet ashing methods were used for digestion of the samples and these two decomposition methods were compared. Manganese was determined by name atomic absorption spectrometry using both direct measurements and the optimized enrichment method. The enrichment was achieved by adsorption of the Mn complexes with cupferron on the activated carbon. The parameters that are thought to affect the recovery of Mn such as type of complexing reagent, acidity and stirring time as well as the influence of the amount of cupferron and activated carbon was investigated individually. The optimum lowest pH value was found as 5.3 by using cupferron. The relative standard deviation was found to be 3% for concentration of Mn 100 mu g l(-1). The detection limit of Mn for the optimized enrichment method was 1.8 mu g l(-1).
Keywords: atomic absorption spectrometry; manganese determination; activated carbon enrichment; cupferron; vegetables